Diversity of benthic microbial mats in five lakes on Sôya Coast ice-free areas, East Antarctica - Koyama, Hiroshi; Wada, Tomotake; Kudoh, Sakae; Imura, Satoshi; Kviderova, Jana; Simek, Miloslav; Verleyen, Elie; Wilmotte, Annick; Elster, Josef (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OB] Polar Biology, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object